ANALISIS PENGARUH LINGKUNGAN KERJA, PENGEMBANGAN KARIR DAN TANGGUNG JAWAB KERJA TERHADAP KEPUASAN KERJA PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA DI KOTA BINJAI - Shintya Shintya; Emi Wakhyuni (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
The research analysis aims to find out whether the work environment, career development and work responsibilities affect job satisfaction. The data analysis technique used is an associative research method with the help of the SPSS version 19 program. This research uses multiple linear regression analysis. The sample in this study was 39 respondents. Primary data collection uses a questionnaire. The results of the research show that the tcount value is 2.581 > ttable of 2.02 with a significant value of 0.014 <0.05, so the hypothesis H3 is accepted and H0 is rejected, meaning that the work environment has a partially positive and significant effect on job satisfaction at the Personnel and Resource Development Agency Humans in Binjai City. The t value is 0.854 < t table of 2.02 with a significant value of 0.399 > 0.05, so the hypothesis H2 is rejected and H0 is accepted, meaning that career development does not have a partially significant effect on job satisfaction at the Personnel and Human Resources Development Agency in Binjai City . The t value is 2.581 > t table is 2.02 with a significant value of 0.014 < 0.05, then the hypothesis H3 is accepted and H0 is rejected, meaning that responsibility has a partially positive and significant effect on job satisfaction at the Personnel and Human Resources Development Agency in Binjai City . The t value is 2.581 > t table of 2.02 with a significant value of 0.014 < 0.05, so the hypothesis H3 is accepted and H0 is rejected, meaning that the work environment, career development and responsibility have a significant effect simultaneously on job satisfaction at the Personnel and Resource Development Agency Human Resources in Binjai City.